(untitled) (Health Renaissance, 2014)
Background: Poor hygiene practices and inadequate sanitary conditions play major roles in the increased burden of communicable diseases within developing countries. Objectives: To know the knowledge and practice of the people about the diseases related to water and sanitation and to know the pattern of water related diseases in last one year in that area. Methods: The crosssectional study was conducted from 16th March to 30th March 2008 in Chandragadhi VDC where 203 households were taken as subjects. Convenient purposive sampling technique was applied. Semi-structured questionnaire was used and face to face interview was conducted. Chisquare test was applied to find out the significant difference between various diseases and related to water and sanitation system of the study areas. Results: People drinking untreated water suffered from diarrhea (38.46%) followed by dysentery (9.89%) respectively. People who devoid of latrine facilities suffered from diarrhea (40.74%) followed by dysentery (12.03%) respectively. Almost (38%) of the population under study gets rid of the excreta of their children in the river nearby and (32.5%) throw in the same latrine they use. Almost (66%) people wash their hands with soap water after defecation. Conclusion: A majority of people with knowledge of safe water and sanitation used soap and water for hand washing before meal and after defecation. People drinking untreated water showed significant with water related diseases ie diarrhoea followed by dysentery. DOI: http://dx.doi.org/10.3126/hren.v11i3.9639 Health Renaissance 2013;11(3):241-245